PENGARUH KEBIJAKAN UTANG, KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN JASA SEKTOR PERDAGANGAN, JASA DAN INVESTASI YANG TERDAFTAR DI BEI - Wildan Aldani, - (2019)
The purposive of this research is to examine whether effect the debt policy measured by Debt To Equity Ratio, investment decision measured by Market to book value asset ratio, and dividend policy measured by Dividend Payout Ratio on value of firm at service companies sectors trade, services and investment companies listed on indonesian stock exchange (IDX) period 2014-2017. This research uses non purposive sampling approach with the technique of determination of the sample using purposive sampling method and obtained 15sample companies sectors trade, services and investment and from population of 138 companies with a research period of four years to obtain 60 units of samples. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using data panel regression analysis with E-views 10.0 program with significance level of 5%. The result of the research show that, (1) debt policy (DER) has a significant positive effect on value of firm (PBV), (2) investment decision (MBAR) has significant positive effect on value of firm (PBV), (3) dividend policy (DPR) has no effect on value of firm (PBV).